Model of Corporate Social Responsibility (CSR) Gold Mining for Community Empowerment Batangtoru District of South Tapanuli in North Sumatra Province - Arifin Saleh; Ahmad Hidayah Dalimunth (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Gold mining company PT. Agincourt Resources (PT. AR), which manages the Martabe Gold Mine in Batangtoru District, South Tapanuli Regency, North Sumatra Province, implements corporate social responsibility or Corporate Social Responsibility (CSR). The CSR program is implemented to help those who are classified as poor in the Batangtoru Subdistrict, which is still around 7,019 or 23.7% of the total population. This study aims to obtain a CSR model that is suitable for PT. AR in realizing the empowerment of the Batangtoru community. The expected result is the existence of a CSR model for gold mining for community empowerment. Research methods with a combined quantitative and qualitative approach. This study focused on 15 villages / kelurahan directly affected by mining with a population of 5,086 families and a sample of 370 households. Quantitative data analysis with Structural Equation Modeling (SEM), using IBM® SPSS® Amos 22 software. Qualitative data with typological data analysis. The results of the study show the implementation of CSR PT. Agincourt Resources has a positive influence and can lead to an increase in community empowerment and the multiplier effect of the company's presence. The CSR model that is suitable and suitable for gold mining companies for community empowerment is by implementing CSR in the health sector, strengthening the family economy, social assistance, infrastructure, and education which is then directed to fields related to community empowerment, such as education level, quality of health facilities, employment, economic centers, infrastructure, increased family assets, increased income, ability to work together, and the ability to obtain information and communication.